THE ORIGIN OF BRIGHTNESS VARIATIONS IN BC CYGNI - Rohanidazegan, M.; Turner, D. G.; Pastukhova, E. N.; Berdnikov, L. N. (Одеські астрономічні публікації, 2017)
The variability of the type C semi-regular (SRC) M3.5 Ia supergiant variable BC Cyg is examined with reference to measurements of its photographic B magnitude derived from 866 archival plates in the Harvard and Sternberg collections and eye estimates of its visual V magnitude made by members of the AAVSO. The star is the brightest member of the cluster Berkeley 87, so it has a well established reddening, distance, and age. BC Cyg exhibits interesting features in its century-long baseline of brightness variations that relate to pulsation and evolution: an 0m.5 increase in (B) over the past century in conjunction with a decrease in pulsation period from ~ 700d to 687d. Associated colour changes imply that the star is hottest when brightest visually or photographically, coolest when faintest visually or photographically. Despite the increase in (B), the star's luminosity appears to have decreased over the past century, presumably as a result of stellar evolutionary effects.